2020
DOI: 10.3389/fphys.2019.01635
|View full text |Cite
|
Sign up to set email alerts
|

Fermented Animal Source Protein as Substitution of Fishmeal on Intestinal Microbiota, Immune-Related Cytokines and Resistance to Vibrio mimicus in Freshwater Crayfish (Cherax cainii)

Abstract: A feeding trial was carried out to evaluate the effects of substitution of fishmeal (FM) by dietary poultry by-product meal, fermented by Lactobacillus casei and Saccharomyces cerevisiae on growth, intestinal health, microbial composition, immune related cytokines and disease resistance of freshwater crayfish, marron (Cherax cainii) against Vibrio mimicus. Two isonitrogenous and isocaloric diets were formulated by replacing FM protein with fermented poultry by-product meal (FPBM) protein at 0% (Control) and 75… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 74 publications
0
20
0
1
Order By: Relevance
“…In the gut, Aeromonas , Candidatus Bacilloplasma, Hafnia Obesumbacterium, Shewanella and Vibrio were identified as resident bacteria, which are capable of growing independently despite changes in dietary compositions. These observations are consistent with the findings of previous studies conducted on various dietary supplements (Foysal et al ., 2019a; Siddik et al ., 2020) and altered environmental conditions (Foysal et al ., 2020a). Of late, studies on crayfish under different feeding regimes (Shui et al ., 2020) and developmental stages (Zhang et al ., 2020) have reported C .…”
Section: Discussionmentioning
confidence: 99%
“…In the gut, Aeromonas , Candidatus Bacilloplasma, Hafnia Obesumbacterium, Shewanella and Vibrio were identified as resident bacteria, which are capable of growing independently despite changes in dietary compositions. These observations are consistent with the findings of previous studies conducted on various dietary supplements (Foysal et al ., 2019a; Siddik et al ., 2020) and altered environmental conditions (Foysal et al ., 2020a). Of late, studies on crayfish under different feeding regimes (Shui et al ., 2020) and developmental stages (Zhang et al ., 2020) have reported C .…”
Section: Discussionmentioning
confidence: 99%
“…Probiotic in aqua diets, has positive influence on the growth and immune performance of commercially farmed shrimp and crayfish species. Among the probiotic bacteria, Lactobacillus species are widely used for their beneficial role in health and immunity of crayfish, Astacus leptodactylus and C. cainii 29,41 . Present study evaluated the combined effects of two most potent LAB on growth, hemolymph parameters, biochemical compositions of tail muscle, intestine and hepatopancreas structure, gut microbiota and immune genes of freshwater crayfish marron.…”
Section: Discussionmentioning
confidence: 99%
“…This upregulation was significant due to the pro and anti-inflammatory mechanisms, aquatic animals balanced the immune response for better defence against stress and infection 56 . Though the presence of cytokine family genes in crustacean tissue including crayfish are evident 41,[75][76][77][78][79] , however, their role have not been studied yet. Hence, further transcriptomic analysis of mRNA is recommended to identify the expressed genes under cytokine family and its level of expression in the intestinal tissue of marron.…”
Section: Discussionmentioning
confidence: 99%
“…LAB has been proven to be effective in modifying the host-associated intestinal microbiota ( Xia et al, 2018 ; Ringo et al, 2020 ). The intestinal microflora play an important role in fish, such as participating in a variety of physiological functions including feed digestion, reduction of the invasion of pathogenic bacteria, and synthesis of the trace elements, amino acids, and vitamins ( Mente et al, 2016 ; Gao et al, 2019 ; Siddik et al, 2020 ). It is well known that various factors could alter the composition of intestinal microorganisms, such as direct-fed microorganisms or diet composition ( Fan et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The activity and composition of intestinal microbiota influences intestinal environments, and therefore cytokines profiles in intestinal content ( Liu et al, 2013 ) which exert vital influence on intestinal health. These cytokines may contribute to the regulation immune response and maintenance of homeostasis of the immune system, enhancement of host defense mechanism against bacteria and fungi ( Siddik et al, 2020 ), lysozyme synthesis, and bactericidal activities ( Giri et al, 2015 ). For example, Jang et al (2020) reported that probiotics inspired pro-inflammatory responses by promoting proinflammatory (TNF-α, IL-6, and IL-1β) and anti-inflammatory cytokine (IL-10) production.…”
Section: Discussionmentioning
confidence: 99%